Salivary hormones and IgA in relation to physical performance in football - Peñailillo, L.; Maya, L.; Niño, G.; Torres, H.; Zbinden-Foncea, H. (Journal of Sports Sciences, 2015)
Salivary biomarkers have shown to be useful to assess physiological stress in football, but their relationship with physical performance is unknown. The aims of this study were to investigate the effect of a football match on salivary cortisol, testosterone and immunoglobulin A (IgA) concentrations in elite footballers, and to examine the relationship of physical performance during the match to these biomarkers. Nine elite football players were assessed before, during and after a friendly international match. Physical performance during the match was measured by time-motion analysis, whilst salivary cortisol, testosterone and IgA were measured before and 10 min post-match. The results showed that players covered an average of 9463 ± 458 m during the match. Salivary cortisol did not change post-match. Testosterone and IgA concentrations decreased by 30.6% and 74.5%, respectively. The testosterone/cortisol (T/C) ratio decreased by 64.2% after the match. Changes in testosterone concentrations correlated (r = 0.85) with distance covered. Pre- and post-match testosterone levels correlated with post-match IgA concentrations (r = 0.8 and 0.89, respectively). These results suggest that a football match induces catabolic stress as indicated by the decreased T/C ratio. It seems that footballers with smaller decreases in testosterone levels covered more distance and decreased their immune function less.